Developing library leaders in Ghana - Badu, E.E.; Dadzie, P.S. (Journal of Education Research and Behavioral Sciences, 2014)
This study explores various leadership approaches i n the context of Ghanaian university libraries. Twenty-six senior librarians and faculty from the U niversity of Ghana were interviewed to determine their views on leadership styles, skills, training and barriers to developing library leaders. Finding s revealed that leaders can be developed through shor t courses, workshops, seminars and formal training. The biggest barrier to library leadership development in Ghana is attributed to shortage of funds for training. The study is limited to the Uni versity of Ghana librarians and faculty of the Department of Information Studies. Therefore, gener alizing to other library staff may be overstretching the conclusions. Nevertheless, there are important lessons to be learnt by all. The study recommends the need for training to be taken seriously in Ghan aian libraries. Additionally, the Department of Information Studies which is the only training scho ol for librarians and archivists was tasked to crea te specific leadership programmes in the curriculum.
Keywords: Leaders; library; leadership; skills; Ghanaian